2022
DOI: 10.3390/children9111630
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Experience and Regulation in Juvenile Primary Headaches: A Cross-Sectional Pilot Study

Abstract: A headache is the most common neurological symptom in children. Its subtypes are migraine (MH) and tension-type headache (TTH). Internalizing rather than externalizing symptoms are more frequent in children with headaches, but little is known about the reasons why. We aim to: (a) examine the interplay between emotional experience, affective regulation, and internalizing symptoms in children suffering from primary headaches and their caregivers; (b) identify potential predictors of children with migraines’ inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…They suggested that the COVID-19 pandemic led to increase in internalizing and externalizing symptoms, and a higher level of stress in parents can be related to the internalizing symptoms of their children ( 32 ). Primary headaches has a higher prevalence of internalizing symptoms such as anxiety, depression, and somatic complaints ( 33 ). However, our study confirmed that “depressive mood” and “conflict with family” were relatively less affected by COVID-19 than other items because most of the participants were elementary and middle school students.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the COVID-19 pandemic led to increase in internalizing and externalizing symptoms, and a higher level of stress in parents can be related to the internalizing symptoms of their children ( 32 ). Primary headaches has a higher prevalence of internalizing symptoms such as anxiety, depression, and somatic complaints ( 33 ). However, our study confirmed that “depressive mood” and “conflict with family” were relatively less affected by COVID-19 than other items because most of the participants were elementary and middle school students.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study compared children with primary headache and their mothers/caregivers to a matched control group and made an assessment of parents and children for emotional awareness using the Emotion Awareness Questionnaire, emotional experience using the Positive and Negative Affect Schedule and psychological adjustment using the Strength and Difficulties Questionnaire [ 40 ]. High headache frequency, regardless of the headache subtype, was closely related to the child’s emotional well-being.…”
Section: Predictors Of Psychological Comorbidities Of Headache In Chi...mentioning
confidence: 99%
“…High headache frequency, regardless of the headache subtype, was closely related to the child’s emotional well-being. Also interestingly, the mother of children with high-frequency headaches had experienced less emotional clarity (DERS), and their children experienced overall more adjustment difficulties [ 40 ].…”
Section: Predictors Of Psychological Comorbidities Of Headache In Chi...mentioning
confidence: 99%